2014
DOI: 10.1002/14651858.cd007450.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure lowering efficacy of partial agonist beta blocker monotherapy for primary hypertension

Abstract: There was very low quality evidence that in patients with moderate to severe hypertension, partial agonists lowered peak BP by an average of 8/4 mmHg and reduced heart rate by five beats per minute. There was no evidence of a greater effect at doses higher than the initial doses. This estimate was probably exaggerated as it was subject to a high risk of bias. Based on the indirect comparison of the results in this review and two Cochrane reviews on angiotensin-converting-enzyme (ACE) inhibitors and angiotensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Phentolamine, 35 an anti-hypertensive drug ( 11i ), also reacted efficiently. Lastly, indolebased molecules such as pindolol ( 11j , a β-blocker) 36 and serotonin ( 11k , a neurotransmitter) 37 provided the corresponding products in high yields in the presence of the copper reagent.…”
Section: Resultsmentioning
confidence: 99%
“…Phentolamine, 35 an anti-hypertensive drug ( 11i ), also reacted efficiently. Lastly, indolebased molecules such as pindolol ( 11j , a β-blocker) 36 and serotonin ( 11k , a neurotransmitter) 37 provided the corresponding products in high yields in the presence of the copper reagent.…”
Section: Resultsmentioning
confidence: 99%
“…first-line therapy for hypertension. [56][57][58][59][60][61][62] In total, these meta-analyses included 316 RCTs. We excluded the trials and trial arms of medications and medication dosages that were not indicated in the BNF.…”
Section: Evidence Base For Medicationsmentioning
confidence: 99%
“…We believe that this is the first example of C2-selective tryptophan deuteration. Efficient C2- and C3-deuteration of the clinically approved beta blocker pindolol/Visken was achieved ( 4l : 57% D incorporation at C2 and 34% at C3); however, no reduction of C3-deuteration was observed after treatment with K 2 CO 3 , even when 3 equivalents of the base were used.…”
Section: Reaction Scopementioning
confidence: 99%